IMPROVING LITERACY SKILLS THROUGH WRITING DRILLS OF THE SECOND YEAR STUDENTS OF SMP 1 PALEMBANG - Retika Wista Anggraini (Global Expert: Jurnal Bahasa dan Sastra, 2016)
The purpose of this study to find out whether or not writing drills to improve the second year students’ literacy skills as observed at SMP Negeri 1 Palembang. The population of this study consisted of eight classes with 156 male students and 154 female students. The population of this study are 320 students of the second year students of SMP Negeri 1 Palembang. The total number of sample was 80 students. A quasi experimental method was used in this study. The data collected by means of a pre-test given to both groups before the treatment and a post-test given after the treatment to both groups. To check whether the application of the instruction could run well as it was designed. the students were evaluated using t-test analysis of statistical product and service solution (SPSS) version 12 to run the analyses and interpreted quantitatively and qualitatively to satisfy the objectives of the study. The result showed that there was a significant acceleration in terms of the students’ reading and writing skills, and there was a positive respond towards this instruction. In conclusion, writing drills can improve the second year students’ literacy skills. Thus, the proposed instruction for reading and writing skills through writing drills either conceptually or practically is plausible to apply in any subjects, especially in reading and writing classes.Key Words :literacy skills, writing drills